2013
DOI: 10.1002/adfm.201303010
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Hybrid Solar Cell Made from CdSe/CdTe Nanocrystals Supported on Reduced Graphene Oxide and PCDTBT

Abstract: Core/shell tetrapods synthesized from CdSe and CdTe exhibit a type II band offset that induces separation of charge upon photoexcitation and localizes carriers to different regions of the tetrahedral geometry. CdSe/CdTe nanocrystals immobilized on oleylamine‐functionalized reduced graphene oxide (rGO) sheets can be homogeneously mixed with an organic dye (PCDTBT) to form donor–acceptor dispersed heterojunctions and exhibit a high power conversion efficiency of ∼3.3% in solar cell devices. The near‐IR light abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…The 2D structure of graphene provides a scaffold to anchor metallic and semiconducting nanoparticles and thus to develop various hybrid assemblies. 30 Graphene's capability to interact with the excited states of semiconducting nanoparticles and undergo charge transfer by monitoring the emission life time of ZnO nanoparticles-graphene (inorganic-organic) composite-based samples is already reported in the literature. 31 The crystal structure of graphene is 2D hexagonal and ZnO exists in hexagonal wurtzite form; thus, there is very good lattice compatibility between the two.…”
mentioning
confidence: 96%
“…The 2D structure of graphene provides a scaffold to anchor metallic and semiconducting nanoparticles and thus to develop various hybrid assemblies. 30 Graphene's capability to interact with the excited states of semiconducting nanoparticles and undergo charge transfer by monitoring the emission life time of ZnO nanoparticles-graphene (inorganic-organic) composite-based samples is already reported in the literature. 31 The crystal structure of graphene is 2D hexagonal and ZnO exists in hexagonal wurtzite form; thus, there is very good lattice compatibility between the two.…”
mentioning
confidence: 96%
“…In functionalized-graphene (f-G), the functional groups can act as anchor sites for inorganic NCs and prevent their aggregation. 22 Furthermore, modification of the graphene surface with QDs causes fluorescence quenching due to the electrons flowing from the conduction band of the QD to the graphene sheets. 23 Therefore, the hybrid nanostructures based on graphene can be considered as the potential acceptor material for organic solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] The resulting heterostructure interface was used to cage photoinduced electrons and consequently separate generated electron-hole pairs. [26] Additionally, n-n junctions heterostructures such as the ones found in structures of silver phosphate/ iron oxide (Ag3PO4/ Fe2O3), [27] silver vanadate/ zinc oxide (Ag3VO4/ ZnO), [28] or zinc oxide/ silver bromide/ iron oxide/ silver vanadate (ZnO/ AgBr/ Fe3O4/ Ag3VO4) [29] have recently been used to promote efficient separation of the charge carriers and generate high efficiency photocatalysis systems based on delayed electron-hole recombination effects. Further, it was also showed that the large surface area of graphene (GO) for instance, [30] its zero bandgap, [31] excellent electrical conductivity and ability to enhance electron transport, [32] its exceptional transparency, [33] and good chemical stability, [34] could lead to its integration as a promoter of photocatalytic reactions in heterostructures.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%